Factorising Double Brackets

Easy

Medium

Difficult

Q1) \(x^2 + 10x + 9\)=
Q1) \(x^2 + 2x -8 =\)
Q1) \(6 x^2 + 17 x+ 7= \)
Q2) \(x^2 + 14x + 48\)=
Q2) \(x^2 -2x -8 =\)
Q2) \(8 x^2 + 10 x+ 3= \)
Q3) \(x^2 + 16x + 64\)=
Q3) \(x^2 + 3x -10 =\)
Q3) \(8 x^2 + 18 x+ 7= \)
Q4) \(x^2 + 11x + 24\)=
Q4) \(x^2 + 4x -12 =\)
Q4) \(6 x^2 + 11x+ 3= \)
Q5) \(x^2 + 11x + 30\)=
Q5) \(x^2 -x -12 =\)
Q5) \(9 x^2 + 6 x+ 1= \)
Q6) \(x^2 + 8x + 7\)=
Q6) \(x^2 -x -6 =\)
Q6) \(6 x^2 + 17 x+ 5= \)
Q7) \(x^2 + 6x + 8\)=
Q7) \(x^2 -4x -12 =\)
Q7) \(4 x^2 + 8 x+ 3= \)
Q8) \(x^2 + 11x + 18\)=
Q8) \(x^2 -3x -10 =\)
Q8) \(8 x^2 + 30 x+ 7= \)
Q9) \(x^2 + 9x + 8\)=
Q9) \(x^2 + x -6 =\)
Q9) \(4 x^2 + 16 x+ 7= \)
Q10) \(x^2 + 11x + 28\)=
Q10) \(x^2 + x -2 =\)
Q10) \(4 x^2 + 4 x+ 1= \)